1992
DOI: 10.1103/physrevlett.69.1777
|View full text |Cite
|
Sign up to set email alerts
|

Friction and wear of Langmuir-Blodgett films observed by friction force microscopy

Abstract: Lubrication is documented on a microscopic scale with a friction force microscope. A reduction in friction is observed for Langmuir-BIodgett film-covered surfaces, compared to the bare substrates. Film defects not detected in the topographic mode are clearly recorded in the friction force mode. With applied forces over 10 nN, the initial stages of wear are observed. Small islands of bilayer height are moved in their entirety, conserving the normal orientation of the aliphatic chains. This collective motion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
112
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(123 citation statements)
references
References 17 publications
11
112
0
Order By: Relevance
“…Although OFMs have been in use for almost a century [2], there is still considerable debate about the nature of the boundary films that they form. Much research has shown that vertically-oriented monolayers of OFMs deposited on surfaces by Langmuir-Blodgett techniques can produce low friction and this is believed to originate from the low shear strength of the interfacial region between the ends of opposing monolayers on the rubbing surfaces [3][4][5]. Some research has also shown that saturated chain OFMs can self-assemble from solution in oil onto solid surfaces to form full or partial, nearly vertically-oriented monolayers and that this results in low friction [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Although OFMs have been in use for almost a century [2], there is still considerable debate about the nature of the boundary films that they form. Much research has shown that vertically-oriented monolayers of OFMs deposited on surfaces by Langmuir-Blodgett techniques can produce low friction and this is believed to originate from the low shear strength of the interfacial region between the ends of opposing monolayers on the rubbing surfaces [3][4][5]. Some research has also shown that saturated chain OFMs can self-assemble from solution in oil onto solid surfaces to form full or partial, nearly vertically-oriented monolayers and that this results in low friction [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Our knowledge of such thin films has increased greatly in recent years due to the development of faster computers and new experimental techniques. Examples of the latter include atomic force microscopy [1,2], the quartz crystal microbalance [3], and the surface forces apparatus (SFA) [4,5,6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The techniques of near field microscopies play a privileged role in the characterization of LB films [12][13][14][15][16][17][18]. Atomic Force or Scanning Force Microscopy (SFM) appears to be a powerfull tool for imaging these systems at a molecular level.…”
mentioning
confidence: 99%